The Role of Socioeconomic Conditions and Psychological Factors in the Willingness to Volunteer for Phase I Studies - Almeida, Luis; Falcão, Amílcar; Coelho, Rui; Albino-Teixeira, António; Soares-da-Silva, Patrício (Pharmaceutical medicine, 2008)
Aim: To assess the role of socioeconomic conditions and psychological factors in the decision of healthy subjects to participate in a phase I study. Methods: Subjects (n = 117) were given information about a phase I study and asked to participate. Subjects were assessed regarding their demographic and socioeconomic characteristics, and evaluated using the Curiosity and Exploration Inventory (CEI-T), Self-Efficacy Scale (SES), State-Trait Anxiety Inventory (STAI), Fear of Negative Evaluation (FNE) and Social Avoidance and Distress (SAD) scales, and the Beck Depression Inventory-II (BDI-II). Results: In a univariate analysis, a significant positive correlation (Spearman’s rho) was found between willingness to participate in the proposed phase I study and CEI-T exploratory tendencies ( R = 0.338; p < 0.001) and total scores ( R = 0.276; p < 0.01), SES total scores ( R = 0.299; p < 0.01) and SES subscales for initiative and persistence ( R = 0.290; p < 0.01), planning/goal setting ( R = 0.189; p < 0.05) and social self-efficacy ( R = 0.294; p < 0.01). A significant negative correlation was found between willingness to participate and STAI anxiety-state ( R = −0.229; p < 0.05), STAI anxiety-trait ( R = −0.260; p < 0.01) and SAD ( R = −0.204; p < 0.05) scores. In a logistic regression model, CEI-T exploratory tendencies, SES initiative and persistence, and STAI anxiety-trait were the only unique significant predictors of willingness to participate in the proposed phase I study (all p < 0.05). Yet, although subjects who refused and those who were willing to participate were significantly different in these personality traits, they showed no marked differences in their demographic or socioeconomic characteristics, including monthly income. A significant positive correlation was found between CEI-T exploration scores and willingness to participate without financial reward ( R = 0.269; p < 0.05). There was an inverse correlation between perceived risk of participation and willingness to participate ( R = −0.236; p < 0.05). Conclusion: Subjects higher in initiative, persistence and exploratory tendencies, and lower in anxiety-traits were more willing to accept participation in a phase I study. These personality traits had a more decisive influence on the subjects’ willingness to volunteer for a phase I study than socioeconomic conditions, such as monthly income.